Commitment, Satisfaction, and Performance of Students at Sekolah Tinggi Ilmu Ekonomi Galileo Batam Indonesia - Hazriyanto; Ibrahim, Badaruddin (International Journal of Psychosocial Rehabilitation, 2020)
The development of education in the college currently concentrates on the development of a human resource, which ranges from staff and lecturers to students. In carrying out academic activities, the college is not separated from the activities and learning process that involve students. Various problems are often faced by universities, especially in the environment of Sekolah Tinggi Ilmu Ekonomi (STIE) Galileo Batam, Indonesia. The problems were directly related to students, as in services, learning environment, commitment, satisfaction, and learning achievement. Based on the problem found, researchers conducted research that focused on the commitment, satisfaction, and performance of students at STIE Galileo Batam. The problem formulation in this study was how the commitment, satisfaction, and performance of male and female students at STIE Galileo? The objective of the study was to know the level of commitment, satisfaction, and students’ performances based on gender. The samples in this study were 33 students of STIE Galileo College. The test used was statistics of SPSS, and in data analysis, researchers applied descriptive analysis. The results show that the commitment and satisfaction of both male and female students as a whole are in the high category. While the overall performance of the students is at a good stage. Researchers who will do further research should have deeper attention, such as on motivation to learn facilities and learning motivation that are not investigated in this research.